Supporting Collaborative Writing with Microtasks - Teevan, Jaime; Iqbal, Shamsi; von Veh, Curtis (CHI 2016, 2016)
This paper presents the MicroWriter, a system that decomposes the task of writing into three types of microtasks to produce a single report: 1) generating ideas, 2) labeling ideas to organize them, and 3) writing paragraphs given a few related ideas. Because each microtask can be completed individually with limited awareness of what has been already done and what others are doing, this decomposition can change the experience of collaborative writing. Prior work has used microtasking to support collaborative writing with unaffiliated crowd workers. To instead study its impact on collaboration among writers with context and investment in the writing project, we asked six groups of co-workers (or 19 people in total) to use the MicroWriter in a synchronous, collocated setting to write a report about a shared work goal. Our observations suggest ways that recent advances in microtasking and crowd work can be used to support collaborative writing within preexisting groups.